2018
DOI: 10.1186/s12906-018-2309-3
|View full text |Cite
|
Sign up to set email alerts
|

Weipixiao attenuate early angiogenesis in rats with gastric precancerous lesions

Abstract: BackgroundAngiogenesis is a pathobiological hallmark of gastric cancer. However, rare studies focus on angiogenesis in gastric precancerous lesions (GPL). Weipixiao (WPX), a Chinese herbal preparation, is proved clinically effective in treating GPL. Here, we evaluated WPX’s anti-angiogenic potential for GPL, and also investigated the possibility of its anti-angiogenic mechanisms.MethodsHPLC analysis was applied to screen the major chemical components of WPX. After modeling N-methyl-N′-nitro-N-nitrosoguanidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
(39 reference statements)
1
23
0
1
Order By: Relevance
“…Weipiling (WPL) is based on an improved version of Sijunzi decoction. Weipixiao, another Chinese medicine formula, also based on the Sijunzi decoction, has shown a certain protective effect on precancerous lesions [13]. Weipiling can be prepared from conventional decoction of eight Chinese medicinal herbs including Hedysarum multijugum Maxim(Huang-qi), Pseudostellaria heterophylla (Miq.)…”
Section: Introductionmentioning
confidence: 99%
“…Weipiling (WPL) is based on an improved version of Sijunzi decoction. Weipixiao, another Chinese medicine formula, also based on the Sijunzi decoction, has shown a certain protective effect on precancerous lesions [13]. Weipiling can be prepared from conventional decoction of eight Chinese medicinal herbs including Hedysarum multijugum Maxim(Huang-qi), Pseudostellaria heterophylla (Miq.)…”
Section: Introductionmentioning
confidence: 99%
“…Blood activating and stasis removing (BASR) is the main principle in traditional Chinese medicine for treatment of cardiovascular diseases. Previous studies have reported that BASR-CHMs promote angiogenesis by upregulating vascular endothelial growth factor (VEGF) gene in the ischemic model (Xin et al, 2018; Zheng et al, 2018; Shi et al, 2019) and inhibit angiogenesis mainly by downregulating VEGF and decreasing MMP9 expression in tumor tissues (Zeng et al, 2018). There are also reports in the literature of the side effect caused by BASRs in abnormally promoting normal blood vessel growth (Su et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…e use of herbal medicine within this system has been viewed as an effective measure to prevent chronic diseases. It has been proven that the use of TCM is effective in blocking and reversing majority of GPL developments [16][17][18]. As shown in Figure 1, this paper elucidates forms of TCM treatment for the prevention and treatment of GPL, including herbal formulations and TCM active ingredients.…”
Section: Introductionmentioning
confidence: 95%
“…Activated HIF-1α in tumor cells can increase the expression and activity of glycolytic enzymes, including GLUT1 and HK2, to accelerate the glycolytic rate [103]. Chinese medicine prescriptions such as Weipixiao formula and Weiqi decoction have been proven to attenuate GPL by suppressing levels of HIF-1α [16,39], suggesting their potential antiglycolytic function.…”
Section: Inhibition Of Glycolysis Aerobic Glycolysis or Thementioning
confidence: 99%
See 1 more Smart Citation